Can health insurance protect against out-of-pocket and catastrophic expenditures and also support poverty reduction? Evidence from Ghana's National Health Insurance Scheme. Issue 1 (December 2016) - Aryeetey, Genevieve; Westeneng, Judith; Spaan, Ernst; Jehu-Appiah, Caroline; Agyepong, Irene; Baltussen, Rob
Abstract Background Ghana since 2004, begun implementation of a National Health Insurance Scheme (NHIS) to minimize financial barriers to health care at point of use of service. Usually health insurance is expected to offer financial protection to households. This study aims to analyze the effect health insurance on household out-of-pocket expenditure (OOPE), catastrophic expenditure (CE) and poverty. Methods We conducted two repeated household surveys in two regions of Ghana in 2009 and 2011. We first analyzed the effect of OOPE on poverty by estimating poverty headcount before and after OOPE were incurred. We also employed probit models and use of instrumental variables to analyze the effect of health insurance on OOPE, CE and poverty. Results Our findings showed that between 7–18 % of insured households incurred CE as a result of OOPE whereas this was between 29–36 % for uninsured households. In addition, between 3–5 % of both insured and uninsured households fell into poverty due to OOPE. Our regression analyses revealed that health insurance enrolment reduced OOPE by 86 % and protected households against CE and poverty by 3.0 % and 7.5 % respectively. Conclusion This study provides evidence that high OOPE leads to CE and poverty in Ghana but enrolment into the NHIS reduces OOPE, provides financial protection against CE and reduces poverty. These findings support the pro-poor policy objective of Ghana's National Health Insurance Scheme and holds relevance to other low and middle income countries implementing or aiming to implement insurance schemes.